Justin Morgan had a horse - Henry, Marguerite 1902-; Dennis, Wesley (New York Scholastic, 1954)
An unusual work horse raised in Vermont and known originally as "Little Bub" becomes the sire of a famous American breed and takes the name of his owner, Justin Morgan.
Keywords: Justin Morgan (Horse) -- Juvenile fiction; Horses -- Juvenile fiction; Justin Morgan (Horse) -- Fiction; Morgan horse -- Fiction; Horses -- Fiction; Vermont -- Fiction